2020
DOI: 10.1002/cpt.1913
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacogenetic Testing and the Posttest Counseling Conundrum

Abstract: Clinical genetic testing for Mendelian conditions is typically coupled with pretest and posttest genetic counseling to support both patients and providers; however, clinical pharmacogenetic testing poses unique characteristics that challenge the traditional role of a genetic counseling service. Given the paucity of professional guidelines on posttest pharmacogenetic counseling, this Perspective highlights key issues currently related to delivering a posttest pharmacogenetic counseling service, including profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The scope of practice for delivering a pharmacogenomic service has been studied and debated (Callard et al, 2012;Mills & Haga, 2013), and a progressive model recently has emerged that leverages the professional competencies of both genetic counselors and pharmacists (Rigobello et al, 2020;Zierhut et al, 2017). The Counseling, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of practice for delivering a pharmacogenomic service has been studied and debated (Callard et al, 2012;Mills & Haga, 2013), and a progressive model recently has emerged that leverages the professional competencies of both genetic counselors and pharmacists (Rigobello et al, 2020;Zierhut et al, 2017). The Counseling, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although education in pharmacogenomics is listed as a practice-based competency by the Accreditation Council for Genetic Counseling (ACGC), >70% of genetic counselors do not feel well-informed about pharmacogenomics (Haga, O'Daniel, et al, 2012), underscoring the need for additional education in test interpretation and communication (Callard et al, 2012). As genetic counselors are increasingly participating directly in clinical pharmacogenomic counseling (Rigobello et al, 2020), we sought to evaluate the landscape of pharmacogenomic education among North American genetic counseling training programs by surveying their administrative leadership.…”
Section: Introductionmentioning
confidence: 99%
“…All focus group participants had experience ordering clinical diagnostic sequencing tests; however, the majority rarely or had not previously ordered pharmacogenomic tests or prescribed medications with established response variability. This was expected, as previous studies have found that physicians generally have limited knowledge of pharmacogenomics, including minimal experience with counseling on these findings without the help of a multidisciplinary care team model [14–18]. An emerging comprehensive pharmacogenomic service model includes physicians, genetic counselors and pharmacists that specialize in pharmacogenomics [1].…”
Section: Discussionmentioning
confidence: 89%
“…Thirdly, the study investigators did not have direct communication or contact with the enrolled patients to return their genotype results and there was no formal documentation of prescriber‐initiated return of results to patients. In the future, this program will include direct return of results to patients in a posttest counseling session 31 . This can be achieved through specialty pharmacy clinics where pharmacogenetics‐trained pharmacists can return results to patients in‐person or via telehealth visits.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, this program will include direct return of results to patients in a posttest counseling session. 31 This can be achieved through specialty pharmacy clinics where pharmacogenetics-trained pharmacists can return results to patients in-person or via telehealth visits. During such sessions, patients can learn about their genotypes and their genotypes' influence on the patients' current and future therapies.…”
Section: Discussionmentioning
confidence: 99%